2012
DOI: 10.1007/s00132-011-1891-6
|View full text |Cite
|
Sign up to set email alerts
|

Ganganalyse nach minimal-invasiver Hüftprothesenimplantation

Abstract: Upon implantation of a hip prosthesis by total hip arthroplasty (THA), clinical criteria are not always sufficient for an objective assessment of the functional outcome. Thus, functional improvement of gait behavior was comparatively validated by instrumented 3D gait analysis for a current, minimally invasive surgical approach (MIS; anterolateral approach) and a conventional, transgluteal approach (KONV). In selected cases, disturbed motion sequences were registered by measuring the muscle activity via high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
2
0
3
Order By: Relevance
“…The present study also showed details of the amplitude drop between the two peaks, representing a period of reduced muscle activation and corresponding to the decline phase just after the weight acceptance peak in the vertical ground reaction force [33, 41]. This level of detail was also likely due to the high time and amplitude resolution.…”
Section: Discussionsupporting
confidence: 52%
“…The present study also showed details of the amplitude drop between the two peaks, representing a period of reduced muscle activation and corresponding to the decline phase just after the weight acceptance peak in the vertical ground reaction force [33, 41]. This level of detail was also likely due to the high time and amplitude resolution.…”
Section: Discussionsupporting
confidence: 52%
“…Ein Jahr postoperativ wurden keine signifikanten funktionellen Unterschiede erhoben (Harris Hip Score, Merle dʼAubigné, SF-36) -die postoperativ durchgeführte Ganganalyse wie auch die CT-gestützte Analyse der Implantatpositionierung ergab keine Unterschiede [55]. Ganganalysen können derzeit durch Beurteilung der kinematischen oder kinetischen Parameter keine Verbesserungen der minimalinvasiven Zugangswege gegenüber konventionellen Zugän-gen belegen [51,54]. Bei minimalinvasiv modifizierten Zugangswegen zum Hüftge-lenk muss des Weiteren eine operative Lernkurve berücksichtigt werden, die möglicherweise in einer erhöhten Komplikationsund Revisionsrate resultieren könnte.…”
Section: Single Incision Techniqueunclassified
“…Nachteile der minimalinvasiven Zugangswege waren eine erhöhte Komplikationsrate, die sich wegen einer eingeschränkten intraoperativen Übersicht in einer erhöhten Rate an Fehlimplantationen äußerte[33]. Zwar ist zum heutigen Zeitpunkt eine Vielzahl an Studien der Evidenzgrade I und II[18,52,54,56,71,72] wie auch Metaanalysen und systematischen Literaturübersichten verfügbar[61][62][63][64][65][66][67][68][69][70], dennoch präsentiert sich die aktuelle Literatur zu vielen Einzelaspekten -wie u. a. zu potenziellen Vor-und Nachteilen, Komplikationen und Revisionsursachen im Langzeitverlauf -limitiert, sodass aus den verfügbaren Metaanalysen[61][62][63][64][65][66][67][68][69][70] keine eindeutige Überlegenheit gegenüber den Standardzugängen hergeleitet werden kann. Auch die Beurteilung der Primärliteratur gestaltet sich äußerst schwierig, da nur wenige kontrollierte Studien existieren, die einen konventionellen Zugang zum Hüftgelenk und dessen minimalinvasive Modifikation vergleichen.…”
unclassified
See 1 more Smart Citation
“…Movement analysis is also used in sports medicine for functional diagnostics and performance analysis [11] and in the rehabilitative sector for therapy management [12]. In orthopaedic trauma surgery care research, instrumental movement analysis is used to evaluate surgical interventions, such as comparison of different implants and surgical approaches [13]. Developments and supplies in orthopaedic technologies and orthopaedic schoe technologies can be planned and checked [14,15].…”
Section: Introductionmentioning
confidence: 99%